Meningkatkan kemampuan literasi anak melalui pendekatan kreatif di era digital - Aliffiana, Bilqis (Maliki Interdisciplinary Journal, 2024)
In the ever-evolving digital era, children's literacy skills are an important key in facing global challenges. Literacy is not only limited to the ability to read and write, but also includes the ability to understand, analyze, and use information critically. This article discusses various creative approaches that can be applied to improve children's literacy, including the use of technology as a learning medium, cultivating reading habits at home, integrating literacy into daily activities, and encouraging creativity through visual and digital literacy. In addition, this article highlights the importance of collaboration between families, schools, and communities in creating an environment that supports children's literacy. With an innovative and interactive approach, children can be more motivated to learn, develop their literacy skills, and become more critical individuals who are ready to face the future.